KEMAMPUAN MEMBACA NYARING SISWA DISLEKSIA SEKOLAH LUAR BIASA PELITA HATI PEKANBARU - Eliza, Nora; ', Auzar; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study aimed to describe the ability of dyslexic school students reading aloud Extraordinary Pekanbaru Pelita Hati. This research is motivated case dyslexic students in grades SMPLB, students have problems in reading. In this study the authors wanted to determine the ability of dyslexic students reading aloud in reading words. The research method used is descriptive quantitative method. The study concluded that the population of this study were 7 students, especially students of dyslexia contained in Special Schools Pekanbaru Pelita Hati. Study data were analyzed descriptively using percentages. RA study indicate income respondents earn an average value of 0.54%, 0.58 RB respondent, respondent RC 0.80, 0.96 RD respondent, the respondent RE 1.00, 0.99 RF respondents, and respondents RG get price -rata 0.98. From the study shows the value of each category of students of high and very high.Keywords: Reading aloud, dyslexia